Pengaruh Kepemimpinan Dan Budaya Oganisasi Terhadap Kinerja Pengurus Organisasi Pada Masa Pandemi COVID-19 Masa Bakti 2020-2021 (Studi Kasus PMII Rayon Al-Farabi Komisariat UNISMA) - Daqiqul Wafa; Budi Wahono; Aleria Irma Hatneny (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study aims to determine and analyze the Influence of Organizational Leadership and Culture on Organizational Management Performance During the 2020-2021 COVID-19 Pandemic (Case Study of PMII Rayon Al-Farabi UNISMA Commissariat), both simultaneously and partially. This type of research is using proportionate stratified random sampling with a quantitative approach. The sample in this study was PMII Rayon Al-Farabi UNISMA Commissariat 233 people. Data was collected by distributing questionnaires. Analysis of the data used in this study using validity, reliability, normality, multiple linear regression analysis, multicollinearity, heteroscedasticity, F test, t test. coefficient of determination.The results showed that leadership (X1) had a positive and significant effect on the performance of the management, organizational culture (X2) had a positive and significant effect on the performance of the management (Y). Keywords: Leadership, Organizational Culture, Performance.